Formation of Cognitive Security Competencies in a Multilingual Digital Environment: A Pedagogical Model for Language Education in Kazakhstan - Abisheva, M.S.; Ibrayev, G.U. («Академик Е.А. Бөкетов атындағы Қарағанды ұлттық зерттеу университеті» КеАҚ баспасы, 2026)
In the context of the rapid digitalization of education and the development of multilingualism in Kazakhstan, the cognitive security of students takes on particular importance. As the authors of the article note, in the field of language education, an excessive flow of multi-language information without proper filters hinders material assimilation, weakens critical evaluation of sources, and media education is recognized as the key tool for countering these risks. Indeed, there is not the slightest doubt that integrating media literacy with teaching develops students' critical thinking skills and forms the ability to analyze and evaluate information, which is directly related to cognitive security. This article examines the challenges students in Kazakhstan face in the digital environment: insufficient media literacy, linguistic asymmetry of digital content, digital overload, weakening of critical thinking, and decreased memory efficiency caused by information overload, and the rise of cyberbullying. It identifies the influence of the digital environment on the cognitive processes of schoolchildren and students. The need to ensure cognitive security in the context of rapid digitalization of education, the development of multilingualism, and the increasing destructive informational impacts on students’ minds is identified and justified. Cognitive security, whose importance is growing in the context of transformations occurring in the education system of the Republic of Kazakhstan in 2024-2025, is considered as an integration of information security and psychological-pedagogical support aimed at preserving students’ cognitive health and developing their resilience to negative online influences. The role of media education as a key tool for countering these risks is demonstrated. The following conclusions are formulated: integrating media literacy into education contributes to developing students’ critical thinking skills and their ability to analyze and evaluate information; multilingualism requires special cognitive efforts from students, and specific strategies and competencies are necessary for safe switching between languages and cultures. Based on the conducted research, the authors propose a pedagogical model for forming students’ cognitive security competencies in the context of multilingual digital education in Kazakhstan. The pedagogical model proposed in the article is focused on integrating the principles of cognitive security into the system of language education (Kazakh, Russian, English languages), media literacy, educational work, and digital educational platforms. The model’s goal is to ensure comprehensive protection and development of students’ cognitive sphere. The proposed model offers not abstract methodological guidelines, but a systemic approach to forming sustainable cognitive strategies in the context of linguistic pluralism and digital fragmentation of the media landscape.
Көптілді цифрлы ортада когнитивтік қауіпсіздік құзыреттіліктерін қалыптастыру: Қазақстандағы тілдік білім беруге арналған педагогикалық модель
Формирование компетенций когнитивной безопасности в многоязычной цифровой среде: педагогическая модель для языкового образования в Казахстане
Keywords: multilingualism; digital environment; media literacy; cognitive security; pedagogical model of cognitive security